2013
DOI: 10.1038/hdy.2013.84
|View full text |Cite
|
Sign up to set email alerts
|

Living on a volcano’s edge: genetic isolation of an extremophile terrestrial metazoan

Abstract: Communities of organisms inhabiting extreme terrestrial environments provide a unique opportunity to study evolutionary forces that drive population structure and genetic diversity under the combined challenges posed by multiple geogenic stressors. High abundance of an invasive pantropical earthworm (and the absence of indigenous lumbricid species) in the Furnas geothermal field (Sao Miguel Island, Azores) indicates its remarkable tolerance to high soil temperature, exceptionally high carbon dioxide and low ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 85 publications
2
41
0
Order By: Relevance
“…Although several complexes of cryptic species have been recently described in earthworms, highlighting the difficulties of morphological diagnosis in this taxon (King et al, 2008;Novo et al, 2010;Pérez-Losada et al, 2009;Shekhovtsov et al, 2016), there is not much data available in the literature on the genetic diversity within the P. corethrurus morphospecies (Cunha et al, 2014;Dupont et al, 2012). In three populations of P. corethrurus in the Azores archipelago, Cunha et al (2014) revealed the existence of two genetically divergent lineages which were morphologically indistinguishable. They showed that one of the lineages was able to cope with the extreme conditions found in the caldera of a volcano where it tolerates a mixture of nonanthropogenic chemical and physical stressors.…”
Section: Evidence Of Cryptic Diversity?mentioning
confidence: 99%
See 2 more Smart Citations
“…Although several complexes of cryptic species have been recently described in earthworms, highlighting the difficulties of morphological diagnosis in this taxon (King et al, 2008;Novo et al, 2010;Pérez-Losada et al, 2009;Shekhovtsov et al, 2016), there is not much data available in the literature on the genetic diversity within the P. corethrurus morphospecies (Cunha et al, 2014;Dupont et al, 2012). In three populations of P. corethrurus in the Azores archipelago, Cunha et al (2014) revealed the existence of two genetically divergent lineages which were morphologically indistinguishable. They showed that one of the lineages was able to cope with the extreme conditions found in the caldera of a volcano where it tolerates a mixture of nonanthropogenic chemical and physical stressors.…”
Section: Evidence Of Cryptic Diversity?mentioning
confidence: 99%
“…), and an average temperature of 17°± 2, where no other tropical species occur. This morphospecies was even recorded in the temperate zone, in the Azores archipelago (Cunha et al, 2014) and the Falkland islands (Reynolds and Jones, 2006). Gates (1972) mentioned that P. corethrurus was present in a greenhouse in the London suburb of Kew (United Kingdom), but there is no record of its expansion in this country.…”
Section: Distribution and Dispersal Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete Pontoscolex corethrurus mitogenome was amplified using seven sets of primers (Table 1) designed based on sequences retrieved from a previous study (Cunha et al 2014). Long PCR targets were amplified using different combinations of the primer sets, and and initially sequenced with the same forward or reverse primers.…”
Section: Mitochondrial Dna Amplificationmentioning
confidence: 99%
“…It is also the most well-known earthworm species in the humid tropics, frequently used in ecological and agronomic studies (Bhattacharjee and Chaudhuri, 2002;Buch et al, 2013;Chapuis-Lardy et al, 2010;Dupont et al, 2012;Hamoui, 1991;Marichal et al, 2010). Being a geophagous endogeic species, P. corethrurus shows high plasticity regarding its tolerance to soil physicochemical characteristics, including variable moisture, high temperatures, exceptionally high carbon dioxide and low oxygen levels, and is capable of inhabiting nutrient-poor soils (Cunha et al, 2014;Hamoui, 1991;Lavelle et al, 1987), as well as rotten logs (Buch et al, 2011).…”
Section: Introductionmentioning
confidence: 99%